2016
DOI: 10.1016/j.jvs.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Value of delayed duplex ultrasound assessment after endothermal ablation of the great saphenous vein

Abstract: Delayed duplex ultrasound assessment after ETA of the GSV comes with associated health care costs but does yield a significant number of patients with progression to EHIT. Better understanding of the timing, risk factors, and significance of EHIT is needed to cost-effectively care for patients after ETA for varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Puggioni et al 33 suggested the use of antiplatelet therapy with serial DUS until resolution and they reserved anticoagulation for those with thrombus progression on surveillance imaging. Ryer et al 34 highlighted that EHIT progression occurred in 13% of patients with Type 1 EHIT managed with just observation, and consequently they proposed anticoagulation for every case of EHIT. These suggestions for the management of EHIT were based upon small sample sizes and no convincing evidence based treatment strategy exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puggioni et al 33 suggested the use of antiplatelet therapy with serial DUS until resolution and they reserved anticoagulation for those with thrombus progression on surveillance imaging. Ryer et al 34 highlighted that EHIT progression occurred in 13% of patients with Type 1 EHIT managed with just observation, and consequently they proposed anticoagulation for every case of EHIT. These suggestions for the management of EHIT were based upon small sample sizes and no convincing evidence based treatment strategy exists.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Considerable variation regarding the timing of postprocedural DUS was noted (Table 1). This may be of considerable significance: Ryer et al 34 noted that 20 out of 842 patients were diagnosed with EHIT on DUS on the first post-procedural day and that an additional 19 cases of EHIT were diagnosed via DUS a week later. Forty-two of the included studies in this review reported that the first postprocedural DUS took place within 1 week; e it is likely that studies with later use of DUS may have missed cases of early EHIT.…”
Section: Discussionmentioning
confidence: 99%
“…Ryer et al investigated 842 patients who underwent great saphenous vein endovenous thermal ablation. All patients were examined by US one day after the procedure, and 79% of patients had the second examination performed one week after the procedure [52]. The EHIT events were more likely in patients with prior DVT and large great saphenous veins, with 5.1% of cases requiring anticoagulant treatment.…”
Section: Specific Thrombotic Complications After Minimally Invasive Tmentioning
confidence: 99%
“…20 Ryer et al identified 43 EHIT diagnoses that required anticoagulation at one week postoperatively, but only 20 of those had been found on an initial ultrasound at 24 hours postoperatively. 21 Some have suggested that postoperative evaluation of DVT is unnecessary, 22 arguing that ultrasound over diagnoses DVT, leading to overtreatment. However, if postoperative ultrasound were reserved for only those with symptoms, a considerable number of DVT would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…9,16 Jones et al also questioned the clinical significance of most forms of EHIT; however, progression to PE has occurred in multiple studies. 9,21,23,24 These occurrences are rare but in the setting of what is generally thought to be an elective procedure are unacceptable. It is unknown whether the true incidence of PE is caused by EHIT; however, our findings suggest that 1.5% of DVTs lead to PE within 7 days and 30 days of an ablation procedure.…”
Section: Discussionmentioning
confidence: 99%